2014
DOI: 10.1016/j.ijid.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Blood stream infections due to OXA-48-like carbapenemase-producing Enterobacteriaceae: treatment and survival

Abstract: Earlier active treatment with colistin based regimens and microbiological and clinical response within 7 days are major predictors of survival in cases of BSIs due to CRE. Rectal screening offers the advantage of earlier recognition and prompt empirical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
4
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 28 publications
2
68
4
6
Order By: Relevance
“…Some studies suggest that for infections due to KPC producers, the use of combination therapy that includes a carbapenem (e.g., polymyxin-carbapenem or aminoglycoside-carbapenem), may reduce the mortality rate (101). Clinical data on the treatment of infections due to OXA-48 and NDM infections are scant; a recent retrospective observational study suggested that for bacteremia due to OXA-48 producers, combination therapy that included colistin reduced the mortality rate (110).…”
Section: Treatment Of Infections Due To K Pneumoniae With Carbapenemmentioning
confidence: 99%
“…Some studies suggest that for infections due to KPC producers, the use of combination therapy that includes a carbapenem (e.g., polymyxin-carbapenem or aminoglycoside-carbapenem), may reduce the mortality rate (101). Clinical data on the treatment of infections due to OXA-48 and NDM infections are scant; a recent retrospective observational study suggested that for bacteremia due to OXA-48 producers, combination therapy that included colistin reduced the mortality rate (110).…”
Section: Treatment Of Infections Due To K Pneumoniae With Carbapenemmentioning
confidence: 99%
“…60 Most of the CRE in these reports are KPC producers, but OXA-48-and NDM-producing CRE are also emerging in patients with hematologic malignancies in locations where these carbapenem resistance mechanisms predominate. 61,62 In one oncology center in India, colistinresistant CRKP have emerged, leaving essentially no therapeutic options for patients infected by these pathogens. 63 CRE are also emerging pathogens in HSCT recipients, particularly after allogeneic transplantation.…”
Section: Cre In Patients With Hematologic Malignancies and Haematopoimentioning
confidence: 99%
“…55 There is some evidence that non-colistin based regimens had worse outcomes than colistin-based regimens. 56 Antibiotics that are active against CRE depend on carbapenemase type, but include polymyxins B and E (colistin), tigecycline, fosfomycin, aminoglycosides, aztreonam, carbapenems (often administered at high doses using prolonged infusion), and the newly approved agent ceftazidime/avibactam. 57 Many of these drugs used in combination with each other or with adjunctive agents like rifampin or minocycline, demonstrate in vitro synergy against CRE.…”
Section: Treatment Implications Of Rapid Detection Of Crementioning
confidence: 99%